"Sociālās palīdzības nodrošinājums personām ar intelektuālo invaliditāti" - Oša, Evija (Latvijas Universitāte, 2014)
Pētījuma mērķis ir izpētīt un noskaidrot, vai Latvijā tiek veicināta sociālo aprūpes pakalpojumu deinstititucionalizācija un vai sociālās aprūpes pakalpojumi tiek nodrošināti tādā kvalitātē, lai pēc iespējas vairāk atbalstītu personas ar intelektuālo invaliditāti. Pētījuma galvenie pamatuzdevumi ir: izpētīt intelektuālās invaliditātes būtību; valsts un pašvaldību atbalstu personām ar intelektuālo invaliditāti; analizēt tiesisko regulējumu starptautiskā, Eiropas un nacionālā līmenī; sniegt savus ieteikumus un komentārus problēmu risināšanā un salīdzināt Latvi

The aim of this study is to explore and find out, whether Latvia promotes social care service deinstitutionalization and whether social care services are provided in such great quality as support for people with intellectual disabilities need. The main tasks of the study is: investigate the nature of intellectual disability; state and local government support system for people with intellectal disabilities; analyze the legal framework for international, European and national level; provide author’s comments and suggestions in solving problems and compare the Latvian legal system in field of intellectual disability with support system in Lithuania, Estonia, Finland and Poland. In the consequence it is found that Latvia needs to create united legistation regulation for people with mental disorders and intellectual disabilities, because of their need for much more complex social care services than for people with functional disabilities. Keywords: intellectual disability, social care,
"Provision of social assistance to persons with intellectual disabilities"
Keywords: Juridiskā zinātne